Sex Differences in the Prevalence, Progression, and Improvement of Chronic Kidney Disease - Kazuyoshi Okada; Mitsuru Yanai; Kazuhisa Takeuchi; Kazuhiro Matsuyama; Kosaku Nitta; Kenji Hayashi; Susumu Takahashi (Karger Publishers, 2014)
Background/Aims: We examined sex differences in prevalence, progression, and improvement in early-stage chronic kidney disease (CKD). Methods: We analyzed data from 533 participants who took 4 consecutive annual CKD detection tests. Results: Urine albumin-creatinine ratio (ACR), estimated glomerular filtration rate (eGFR), and hemoglobin (Hb) at baseline in men with and without CKD and in women with and without CKD were 8.3±6.1, 149.2±310.4, 10.2±5.8, and 96.7±246.8 mg/g Cr; 83.4±14.7, 63.8±18.8, 79.9±13.0, and 69.4±20.0 mL/min/1.73 m2; and 14.8±1.2, 14.3±1.4, 13.0±1.0, and 13.0±1.2 mg/dL, respectively. ACR levels decreased significantly over time in men and women with CKD and they increased significantly over time in men and women without CKD. eGFR levels in men and women with CKD did not significantly change over time, but they decreased significantly over time in men and women without CKD. CKD prevalence and progression rate were not significantly different between sexes. Among the CKD participants, significantly more women had a "cured" status at 3 years (39.1% vs. 19.4%, P60 mL/min/1.73 m2 at 3 years had values just below those at baseline. Regression analysis showed that change in eGFR correlated significantly with ACR in men with CKD (change in eGFR = -1.707+0.022×ACR, Pr2=0.201) and with Hb and ACR in women with CKD (change in eGFR = 48.870-3.803×Hb + 0.018×ACR, Pr2=0.134). Conclusions: These results suggest that the slight decrease of Hb within a normal range and mild anemia can be managed in women with early-stage CKD. The key baseline for eGFR is 60 mL/min/1.73 m2.